An Interesting New Kingdom Stela from Thebes Cairo Museum (CG 34045) - Metawi, Rasha.
The object of this paper is to make known a New Kingdom stela from the Theban necropolis, currently displayed at the Cairo Museum (CG 34045, JE. 4746). The stela belongs to a s?m ‘š n ’Imn named Userhat. It has a distinctive shape showing an outer frame with a rounded top surrounding a representation in high relief of a false door mounted by a human head with two hands raised in adoration. With such unusual composition the object, I assume, was intended to fulfill the roles of two important funerary architectural elements: a false door and a stelophorous statue. The twofold function of the object is supported by the arrangement of its textual and iconographical details that are clearly touching on two themes: the endowment of funerary requests, and the facilitation of the deceased’s daily resurrection with the rising sun, on two main parts (the false door and the round topped outer frame), so that each part would achieve a function. Cairo Museum (CG 34045) can be assigned a date early in the reign of Thotmoses III, on the basis of internal evidence combined with the information provided by two other objects that are very likely belonging to the same s?m ‘š n ’Imn Wsr-h3t (stela St. Petersburg Ermitage no. 1093, and stela National Museum Stockholm, no 42).